A masterly and definitive work. The Treatise of Canonical Procedural Law by Monsignor Juan José Garcia Faílde - Guzmán Pérez, Cristina (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
In the presentation of this Treatise attention is called to its significance in the science of Canon Law and to the author’s wide and important canonical work; its contents are described stressing the most important and original points with an explicit reference to a practical usefulness of the forms it offers.